Longitudinal association between disability and suicide mortality in Republic of Korea - Lee, Hwa-Young; Shin, Dong Wook; Han, Kyung-Do; Kawachi, Ichiro (International journal of epidemiology, 2024)
The Republic of Korea has reported the highest suicide rate globally since 2018. Previous studies have highlighted disability as a significant risk factor for suicide. However, comprehensive examination on the association between suicide mortality and severities and types of disabilities, and on how these associations vary according to sociodemographic characteristics, health behaviours and comorbidity profiles has never been performed. We performed a retrospective cohort study of a nationally representative sample of 3 591 398 individuals subject to the health check-up provided by the Korean National Health Insurance in 2009, including individuals with (n = 126 508) and without (n = 3 734 890) disabilities, and followed-up until December 2021. Overall, the presence of disability was associated with an increased risk of suicide mortality [hazard ratio (HR), 1.38; 95% confidence interval (CI), 1.30-1.47] compared to the absence of disability. This risk was more pronounced in individuals with Grade 1-3 disabilities (HR, 1.68; 95% CI, 1.52-1.85) than those with Grade 4-6 disabilities (HR, 1.28; 95% CI, 1.20-1.47). Among various types of disabilities, individuals with a disability associated with a mental disorder had the highest HR (HR, 4.49; 95% CI, 3.38-5.97), followed by those with visual impairment (HR, 1.47; 95% CI, 1.26-1.73), brain damage (HR, 1.45; 95% CI, 1.18-1.79), hearing impairment (HR, 1.35; 95% CI, 1.15-1.58) and extremity disability (HR, 1.30; 95% CI, 1.21-1.40). Stratified analyses revealed that the suicide risk associated with disabilities was more pronounced in individuals with specific sociodemographic characteristics and health behaviours. Our findings highlight the need to prioritize policy efforts to address suicide mortality among people with disabilities, considering the distinct risks associated with disability types and severity.